Comparison of Honai and Other Traditional Houses' Physical Qualities on Respiratory Diseases - Rifa'i, Sholli Cholik (Departement of Architecture, Universitas Islam Indonesia, 2022)
One of Jayawijaya's traditional houses, Honai, relies much on thermal comfort factors, as most residences are. Honai architecture conforms to Jayawijaya's environment and the Dani tribe's daily activities. The Dani people lit fires inside, and the smoke from the fires caused respiratory diseases among the residents. This study focused on the thermal comfort variables, such as air temperature, humidity, and wind velocity, of the Honai interiors and compared them with those of other traditional houses in Indonesia that also use hearth systems inside. CFD (Computational Fluid Dynamics) simulations were performed to illustrate how the air inside each type of house circulates. The result of the simulations shows that with an adequate area of openings, the smoke from the hearths inside the compared three houses tends to be carried out quickly, while in Honai houses, it requires a relatively longer time for the smoke to be distributed to the outside. This result strengthens the author’s hypothesis, stating that the occupants of Honai houses had respiratory diseases due to the lack of air ventilation in their homes. At the end of the research, the author made a design recommendation for the occupants of Honai houses to add a sufficient area of ventilation to create healthier Honai houses so that the respiratory disease rate in Papua would possibly be reduced. Keywords: Thermal comfort, Honai, respiratory disease, hearth, ventilation, CFD.